1982
DOI: 10.1177/000348948209100219
|View full text |Cite
|
Sign up to set email alerts
|

Functional Patency of the Cochlear Aqueduct

Abstract: The perilymphatic (PP) and cerebrospinal fluid (PCSF) pressures were investigated in relation to pressure variations in the ear canal, middle ear and intracranial compartment before and after occlusion of the cochlear aqueduct (CA). Experiments using intracranial infusion showed that the CA was responsible for a perfect hydrodynamic balance between the CSF and the perilymph. There are indications of additional pressure release factors but their capacities were not sufficient to prevent the appearance of a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 20 publications
2
20
1
Order By: Relevance
“…The consequence of this is that the flow resistance of the cochlear aqueduct and/or the compliance of the membranes bordering the inner ear do not have a constant value. This was also concluded by Densert et al (1978) and by Carlborg et al (1982) based on pressure equalization experiments in cats.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The consequence of this is that the flow resistance of the cochlear aqueduct and/or the compliance of the membranes bordering the inner ear do not have a constant value. This was also concluded by Densert et al (1978) and by Carlborg et al (1982) based on pressure equalization experiments in cats.…”
Section: Discussionsupporting
confidence: 64%
“…Other channels connecting the perilymphatic compartment with the intracranial compartment are the vestibular aqueduct, perineural and perivascular spaces (Cotugno's canal) and the tympanomeningeal or Hyrtl's fissure [9]. Carlborg et al (1982) and later Suzuki et al (1994) have shown that these other transduction routes are less important for inner ear pressure equalization.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence on inner ear volume was explained by round window membrane position influencing aqueduct flow resistance (Wit et al 2003). The study also indicated that aqueduct flow resistance does not depend on flow direction, in contrast with evidence from earlier research (Densert et al 1981;Carlborg et al 1982;Thalen et al 2001Thalen et al , 2002.…”
Section: Introductioncontrasting
confidence: 93%
“…The cerebrospinal fluid is directly connected to the perilymphatic compartment by the co chlear aqueduct, through which fluid and pressure ex change can take place. The function of the cochlear aque duct has been examined extensively in animal experi ments, and its relevance for lower animals is generally accepted [17,18]. In humans, post-mortem temporal bone studies are performed, but the precise physiological function of the cochlear aqueduct in humans remains unclear [19,20], Anatomical studies have shown a de crease in patency of the aqueduct with advancing age [19].…”
Section: Discussionmentioning
confidence: 99%